Локализация и распознавание автомобильных номеров на изображениях - Кийко, В.М. (Управляющие системы и машины, 2017)
Рассмотрены новые алгоритмы поиска и распознавания автомобильных номеров на изображениях. Распознавание номерного знака выполняется путем выделения особых точек на контурах символов и вычисления модифицированного расстояния Левенштейна между входными и эталонными цепочками этих точек. Приведены результаты экспериментальной проверки предложенных алгоритмов. Розглянуто нові алгоритми пошуку і розпізнавання автомобільних номерів на зображеннях. Розпізнавання номерного знаку виконується шляхом виділення особливих точок на контурах символів і обчислення модифікованої відстані Левенштейна між вхідними та еталонними ланцюжками цих точок. Подано результати експериментальної перевірки запропонованих алгоритмів. Purpose. It is important to provide robust license plates recognition under conditions of long-distance and not frontal location of camera relatively to license plate. To reduce processing time it is desired also preliminary to detect a small number of image parts which may contain license plates and precisely localize these plates. Methods. Localization of number plates is based on detection of license plate frame contour lines by Hough transform. While recognition special points in symbol contour are detected and modified Levenstein distances are computed between input and etalon chains of these points. Separation of similar in shape symbols is carried out by detection of additional structural and metrical contour features. Used structural and metrical features of symbols are robust in a great measure to scaling and rotations of symbols in image. Results. The results of experimental testing of the proposed localization and recognition algorithms are presented. Conclusion. Proposed algorithms can be used as basis for new as well as in developed before systems for license plates recognition in images.